Effect of energy allocation in dual‐hop communication systems with DF protocol. Issue 11 (1st May 2018) - Cho, W.
Abstract : Relay communication has been receiving considerable attention for its advantage of extension in communication coverage and enhancement of communication performance. In this Letter, the author studied the performance of dual‐hop communication systems with a decode‐and‐forward protocol. The author first analyses the performance of dual‐hop communication systems with various modulation schemes. Then, the author found the optimum energy allocation depending on the relay location for each modulation scheme. Finally, the performance of dual‐hop communication systems with equal energy allocation and optimum energy allocation was compared.